The influence of atmospheric and oceanographic conditions on the occurrence of Portuguese Man-o-War (Physalia physalis) along the Iberian coasts. The case of summer 2019 and potential future implications - Macias, Diego; García-San Martín, Lorea; Prieto, Laura (Frontiers in Marine Science, 2025)
The pleustonic, open-ocean dweller Physalia physalis can reach European Atlantic coasts when the combination of wind and currents drags the colonies from their typical habitats in the open ocean towards these shores. Usually, this passive advection happens during the winter months, when low-pressure atmospheric systems typically move from west to east accompanied by strong westerly winds. This is particularly fortunate for humans, as most of the presence of these potentially dangerous organisms on beaches occurs during the low tourist season. However, in early summer 2019, a number of P. physalis colonies arrived on the beaches of the southern Iberian Peninsula, causing closures, economic damage, and social concern. Different stakeholders wondered why this unusual event occurred and if it was a sign of change in these organisms’ distribution areas as a consequence of climatic shifts. With the aim of elucidating the potential causes of the atypical arrival of P. physalis colonies during summer months to these important touristic destinations, we utilize the most advanced, freely available, datasets of atmospheric and oceanographic conditions in the affected region. Our study reveals that summer 2019 presented particular atmospheric characteristics, with very low atmospheric pressure on both sides of the Iberian Peninsula and associated westerlies that drove a peculiar oceanographic setting with abnormal eastward currents and larger-than-average waves in the Gulf of Cádiz. All these elements combined drag the free-floating colonies onto the affected beaches and cause social alarm in the affected communities. Even if summer 2019 was unique on record, there are indications that wind and wave conditions along the western European coasts might become more favorable for the arrival of floating organisms from the open ocean in the decades to come, calling for improved monitoring and alert systems in the region.